Riboflavin-Induced Type 1 Photo-Oxidation of Tryptophan Using a High Intensity 365 Nm Light Emitting Diode - Aspee-Lamas, A; Tirapegui-Calquin, C; Barrías-González, P (Elsevier Inc., 2019)
The mechanism of photo-oxidation of tryptophan (Trp) sensitized by riboflavin (RF) was examined employing high concentrations of Trp and RF, with a high intensity 365 nm light emitting diode (LED) source under N2, 20% and 100% O2 atmospheres. Dimerization of Trp was a major pathway under the N2 atmosphere, though this occurred with a low yield (DφTrp = 5.9 × 10−3), probably as a result of extensive back electron transfer reactions between RF•- and Trp(H)•+. The presence of O2 decreased the extent of this back electron transfer reaction, and the extent of Trp dimerization. This difference is attributed to the formation of O2 •- (generated via electron transfer from RF•- to O2) which reacts rapidly with Trp• leading to extensive consumption of the parent amino acid and formation of peroxides and multiple other oxygenated products (N-formylkynurenine, alcohols, diols) of Trp, as detected by LC-MS. Thus, it appears that the first step of the Type 1 mechanism of Trp photo-oxidation, induced by this high intensity 365 nm light source, is an electron transfer reaction between the amino acid and 3RF, with the presence of O2 modulating the subsequent reactions and the products formed, as a result of O2 •- formation. These data have potential biological significance as LED systems and RF-based treatments have been proposed for the treatment of pathological myopia and keratitis. © 2018 Elsevier Inc.